2016
DOI: 10.1021/acscatal.6b00723
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity Control in the Catalytic Dehydration of Methyl Lactate: The Effect of Pyridine

Abstract: Catalytic dehydration of biomass-derived methyl lactate to produce acrylic acid and its esters promises a renewable route to produce a major commodity chemical. Alkali metal cation exchanged zeolites are capable of catalyzing this reaction, however, selectivity control toward the dehydration pathway remains a challenge. Through combined kinetic and transmission spectroscopic investigations, we demonstrate that introducing pyridine, a base, to the reaction feed increases selectivity to acrylates while inhibitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
110
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(125 citation statements)
references
References 50 publications
15
110
0
Order By: Relevance
“…Upon adsorption to NaY at elevated temperatures, more acidic species, i. e., those with lower pK a or GPDE, generate higher densities of Brønsted acid sites (BAS) than less acidic species, suggesting that stronger acidity leads to a higher degree of dissociative adsorption (Figure ). The properties of the NaY sample used in this study have been reported previously, and multiple methods were unable to detect any intrinsic Brønsted acid sites (BAS, Scheme ), including a lack of the 3645 cm −1 band in transmission FTIR spectroscopy attributed to the ν(OH) of BAS and as well as the lack of the 1545 cm −1 band corresponding to pyridinium upon adsorption of pyridine. Thus, the appearance of the spectroscopic feature at 3645 cm −1 in the presence of adsorbed species is attributed to BAS generated from the dissociative adsorption of the organic acids as shown in Scheme .…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Upon adsorption to NaY at elevated temperatures, more acidic species, i. e., those with lower pK a or GPDE, generate higher densities of Brønsted acid sites (BAS) than less acidic species, suggesting that stronger acidity leads to a higher degree of dissociative adsorption (Figure ). The properties of the NaY sample used in this study have been reported previously, and multiple methods were unable to detect any intrinsic Brønsted acid sites (BAS, Scheme ), including a lack of the 3645 cm −1 band in transmission FTIR spectroscopy attributed to the ν(OH) of BAS and as well as the lack of the 1545 cm −1 band corresponding to pyridinium upon adsorption of pyridine. Thus, the appearance of the spectroscopic feature at 3645 cm −1 in the presence of adsorbed species is attributed to BAS generated from the dissociative adsorption of the organic acids as shown in Scheme .…”
Section: Resultsmentioning
confidence: 72%
“…However, the wavenumber of the O−H stretching band of BAS on faujasites is not a reliable descriptor for their acidity . The dissociative adsorption generates a corresponding sodium salt species, which is identified via a unique ν([O−C−O] − ) mode typically located in the range of 1550–1650 cm −1 in FTIR spectroscopy . In a previous study, we demonstrated that molecules with gas‐phase deprotonation enthalpy (GPDE) below ∼1625 kJ/mol generated clear vibrational bands for BAS and corresponding sodium salts when adsorbed on NaY, while molecules with GPDE above this threshold did not.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, no degradation of GD occurred at higher reaction temperatures. This is in sharp contrast to the conversion of MLA, where the decarbonylation of LD or MLA itself with formation of acetaldehyde was observed at reaction temperatures above 220 °C . Because additional methyl groups are lacking on the 6‐membered ring of GD, or on the α‐carbon of MGA, no decarbonylation to acetaldehyde can take place.…”
Section: Resultsmentioning
confidence: 77%
“…Murphy et al. suggested that the formation of acetaldehyde over NaY zeolite is taking place over Brønsted acid sites However, recently Sad et al. reported a study showing that protonic forms of zeolites, viz .…”
Section: Chemical Routes Of Acrylic Acidmentioning
confidence: 99%
“…To reveal a possible reaction mechanism of the dehydration of ML on zeolites, Murphy et al. performed an in‐situ FTIR study of ML conversion over NaY (Scheme ) . They suggested that similar to lactic acid, the first step of the dehydration reaction is a dissociative adsorption of ML on zeolite surface with the intermediate formation of a surface sodium lactate species.…”
Section: Conversion Of Alkyl Lactates and Derivatives To Alkyl Acrylatesmentioning
confidence: 99%